Immunohistochemical and Physiological Research on Farm Animals - Scocco, Paola; De Felice, Elena; Malfatti, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint represents a collection of papers that aimed to highlight the importance of immunohistochemical findings and their role in improving the understanding of organ tissue functions. We focused our attention on farm animals because they represent not only a source of food in the supply chain, but also a source of income for breeders, a source of employment, and a primary tool in the quest for sustainable food production. To achieve this last aim, we asked authors for research that could potentially be applied to the purpose of this study, and whose results could be useful in improving farm management practices and the responsible use of natural resources. A total of 20 papers were contributed to this issue, written by 118 authors from 4 countries, and comprising 18 research articles and 2 communications articles.